Between 'old' and 'new' science: S.Ya. Lurie's life in the crucial time for Russia (late 1910s – early 1930s) - A.A. Mirovshchikova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper reviews the initial period of the creative path of the scientist of antiquity S.Ya. Lurie, who is a famous classical philologist specializing in the field of Ancient Greek history. In 1913 he graduated from the History and Philology Faculty of St. Petersburg University and was left to prepare for the professorship at the Department of Classical Philology. The beginning of his independent scientific and teaching work coincided with the period of global transformations that occurred in Russia in the second half of the 1910s – 1920s. The historian of the “old” school was not able to find a place in the “new” Soviet historical science for a long time. Because of these conditions, the researcher used his knowledge and skills to work for various institutions, including archives, schools, vocational schools and institutes. Despite the hardships of the 1920s, S.Ya. Lurie did not stop his scientific work. Furthermore, he discovered new directions for research and became recognized by foreign specialists in the field of epigraphy. In 1934, the brilliant scientific works of the historian allowed him to receive the Doctor of Historical Sciences degree without defending the dissertation. With the restoration of history teaching in 1934, the scientist was invited to work at the Faculty of History of Leningrad University, where he continued his scientific and teaching activities until 1949.